A Forecasting Analysis on China'S Energy Use and Carbon Emissions Based on A Dynamic Computable General Equilibrium Model. Issue 3 (19th February 2021) - Guo, Zhengquan; Zhang, Xingping; Ding, Yihong; Zhao, Xiaonan
ABSTRACT: This paper constructs a dynamic computable general equilibrium model to forecast China's economy, energy use, and carbon emissions. The fossil energy sector and clean electricity sector are disaggregated in detail to obtain robust results. The analysis results show that the industry and energy structure will obviously change along with a high and stable economy growth trend by 2030. Although energy intensity and carbon emission intensity in China will decrease markedly, carbon emissions will keep rising and will not peak by 2030. Therefore, China's government must adopt effective measures to realize the commitment goal.